Faktor Iklim Dengan Kejadian Pneumonia Di Kota Jakarta Pusat Periode 2016-2020 - Ranti Ekasari; Ummul Radia; Sinjai Sinjai; Andi Abil Hasan Rivai; Noviana Noviana (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2022)
The environment is one factor that can cause health problems. One aspect of the environment that plays a role in the pattern of disease transmission is climate change. This can be seen in the frequency of respiratory and cardiovascular disease events such as pneumonia. This study aimed to determine the relationship between climate, including temperature, humidity, and rainfall, and the incidence of pneumonia in Central Jakarta in 2016–2020. The method used is quantitative research with a descriptive study design. This study used secondary data where climate data was obtained from the Meteorology, Climatology, and Geophysics Agency. Climate data is daily data which is converted into monthly data. While pneumonia data is monthly data for all pneumonia cases recorded at the DKI Jakarta Health Office, which can be accessed online. The data was processed univariately with descriptive analysis and bivariate with correlation analysis. The results showed that the lower the temperature, the higher the pneumonia cases (r = -0.238). However, the higher the humidity (0.145) and the rainfall (0.158), the higher the pneumonia cases. The local government should increase vigilance against the transmission of pneumonia, especially when humidity and rainfall are high and the ambient temperature is low.